New Paradigm of Merdeka Belajar Curriculum in Schools - Abdul Hadi; Marniati Marniati; Rispa Ngindana; Musyarrafah Sulaiman Kurdi; Muqarranah Sulaiman Kurdi; Fauziah Fauziah (AL-ISHLAH: Jurnal Pendidikan, 2023)
Responding to changing times and evaluating the 2013 Curriculum, the Government implemented the Merdeka Belajar to improve human resources and the quality of education. This study aims to describe the Merdeka Belajar Curriculum at school. The research method used is Systematic Literature Review (SLR) with metal synthetic data analysis techniques. This study concludes that the change from the 2013 Curriculum to the Merdeka Belajar Curriculum was caused by several factors, including the quality of human resources, changing times, and the evaluation results of the 2013 Curriculum. Furthermore, the framework for designing the Merdeka Belajar Curriculum is one of the four curriculum options that can be adopted by educational units in the context of learning recovery. The need for implementing this curriculum is due to several advantages, including being simpler and more in-depth, more independent; and more relevant and interactive. However, in implementation, several obstacles were encountered, namely, the teacher's understanding of the curriculum and teacher competence in using technology.